The Judge's Consideration of the Phrase Urgent Reasons in Marriage Dispensation Cases : A Legal Realism Perspective - Ahmad, Ilma Maulana; Alvin Saputra, Muhammad; Habibah, Zahrotul (Yayasan Lembaga Studi Makwa, 2025)
This study examines the increasing number of marriage dispensation cases following the amendment of the minimum marriage age through Law No. 16 of 2019, which reveals a gap between regulatory objectives and social realities. The purpose of this research is to analyze judicial interpretations of the phrase “very urgent reasons” and to identify the social and moral considerations influencing judges’ decisions in marriage dispensation cases. This study employs a qualitative method using a juridical-normative approach, conducted as library-based research. Legal materials were collected from legislation, court decisions, academic literature, and relevant legal documents, and were analyzed descriptively and analytically. The findings indicate that judges possess broad discretionary authority in interpreting “very urgent reasons,” resulting in inconsistent applications due to the absence of clear normative parameters. Judicial reasoning is not limited to formal legal provisions but is strongly influenced by social conditions and moral considerations, particularly the aim of preventing greater harm to the parties involved. This demonstrates that legal practice in religious courts operates as a living law shaped by societal realities. The implications of this research highlight the need for clearer regulatory guidelines to ensure uniform judicial considerations that prioritize child protection and the prevention of early marriage. The contribution of this study lies in offering an analytical framework that explains judicial discretion in marriage dispensation cases. The originality of this research is found in applying an interpretive perspective to reveal the dynamics of legal reasoning within religious courts